THE EFFECT OF PERCEPTION OF CONVENIENCE, E-SERVICE QUALITY, PROMOTION AND PERCEPTION OF RISK ON INTEREST IN USING E-WALLETS AMONG STUDENTS IN YOGYAKARTA - Fahrul Iman Santoso; Nur Ainun (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of perceived ease of use, e-service quality, promotion, and risk perception on the interest in using e-wallets among students in Yogyakarta. The background of this study is based on the rapid development of financial technology that is driving changes in people's transaction behavior towards a cashless system. Although e-wallet use is increasing, the intensity of use is still relatively low, so further study is needed to determine the factors that influence interest in using it. This study uses a quantitative approach with a survey method by distributing questionnaires to 110 respondents who are active students in Yogyakarta and e-wallet users. The data analysis technique used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results show that partially, perceived ease of use and e-service quality do not significantly influence interest in using e-wallets. Meanwhile, promotion is proven to have a positive and significant effect on interest in using e-wallets. Perceived risk also shows a positive and significant effect on interest in using e-wallets, indicating that users still consider the risk aspect in making decisions about using financial technology. Simultaneously, the four variables contributed 31.4% to e-wallet usage interest. This finding implies that effective promotional strategies, along with increased trust and understanding of risks, are crucial factors in increasing e-wallet usage interest among students.